A LONGITUDINAL ANALYSIS OF PHYSICAL FUNCTION, MENTAL HEALTH AND FATIGUE IN LUNG CANCER SURVIVORS. (11th November 2018) - Medysky, M; Lyons, K; Dieckmann, N; Sullivan, D; Winters, K
Abstract: With a median age at lung cancer diagnosis of 70 years, patients may be at risk of poor physical functioning that is accelerated by cancer treatment. However, it is unknown whether all patients experience the same rate of functional decline during treatment or if some patients have more or less severe trajectories. The purpose of this study was to identify trajectories of self-reported physical function in lung cancer survivors and examine whether mental health and fatigue influenced the rate of change. In a sample of 72 newly diagnosed lung cancer survivors (mean age = 71 + 10 years) we used multilevel modeling to assess trajectories of self-report physical functioning and the influence of mental health and fatigue assessed five times over one year. Self-report physical function did not change significantly over the year (□=-0.46, p=0.53); however, there was significant variability within the sample around the average rate of change (p<0.001) suggesting that physical functioning declined for some and improved for others. Mental health and fatigue at baseline were both significant predictors of rate of change in physical function (p<0.001), with higher baseline levels of mental health and lower levels of fatigue associated with slower declines in physical functioning over time. Our data suggest that lung cancer survivors may not all experience the same degree of perceived functional declines and those who report lower mental health and higher fatigue may benefit from interventions, such as exercise, to protect against declines in physical functioning.